2020
DOI: 10.3390/polym12071592
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Composition and Plasma Power on Properties of Film from Biodegradable Polymer Blends

Abstract: The work is focused on the study of surface plasma treatment (DCSBD) of films from biodegradable polymers from renewable sources based on polylactic acid (PLA) and polyhydroxybutyrate (PHB). A 4-factor design of experiment was used where the selected variable parameters were the plasma device power, the time of plasma treatment, the ratio of PHB in the polymer blend with PLA, and the content of acetyl tributyl citrate (ATBC) plasticizer in the PLA + PHB blend. The surface total energy and the polar component w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These changes were described as bubble-shaped structures. It is accepted that this kind of change in surface morphology is assigned to the etching process [47,48]. It is interesting that these bubbleshaped structures were not observed on the surface of the film plasma-modified for 15 min (PET plasma 15min ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes were described as bubble-shaped structures. It is accepted that this kind of change in surface morphology is assigned to the etching process [47,48]. It is interesting that these bubbleshaped structures were not observed on the surface of the film plasma-modified for 15 min (PET plasma 15min ).…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse coplanar surface barrier discharge plasma treatment has also been studied in a set of films made of biodegradable polymers from renewable sources based on polylactic acid and polyhydroxybutyrate. A 4-factor experimental design was used, where the selected variable parameters were the power of the plasma device, the plasma treatment time, the ratio of polyhydroxybutyrate in the polymer mixture with polylactic acid and the content of the plasticizer acetyl tributyl citrate in the polylactic acid with polyhydroxybutyrate mixture [10]. In the plasma treatment of the surfaces of two engineering polymers including polyamide 66 and polytetrafluoroethylene by diffuse coplanar surface barrier discharges in atmospheric air, it was found that the adhesion of polyamide 66 for polymer/polymer or polymer/steel joints was improved, but it was selective for the investigated adhesive agents [11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors wish to make a change to the published paper [1]. We wish to add an affiliation of Leona Omaníková and Ján Bočkaj-CEPLANT, Department of Physical Electronics, Faculty of Science, Masaryk University, Kotlarska 2, 611 37 Brno, Czech Republic.…”
mentioning
confidence: 99%